Induced Neurocysticercosis in Rhesus Monkeys (Macaca mulatta) Produces Clinical Signs and Lesions Similar to Natural Disease in Man - N. Chowdhury; A. Saleque; N. K. Sood; L. D. Singla (The Scientific World Journal)
Neurocysticercosis is a serious endemic zoonosis resulting in increased cases of seizure and epilepsy in humans. The genesis of clinical manifestations of the disease through experimental animal models is poorly exploited. The monkeys may prove useful for the purpose due to their behavior and cognitive responses mimicking man. In this study, neurocysticercosis was induced in two rhesus monkeys each with 12,000 and 6,000 eggs, whereas three monkeys were given placebo. The monkeys given higher dose developed hyperexcitability, epileptic seizures, muscular tremors, digital cramps at 10 DPI, and finally paralysis of limbs, followed by death on 67 DPI, whereas the monkeys given lower dose showed delayed and milder clinical signs. On necropsy, all the infected monkeys showed numerous cysticerci in the brain. Histopathologically, heavily infected monkeys revealed liquefactive necrosis and formation of irregular cystic cavities lined by atrophied parenchymal septa with remnants of neuropil of the cerebrum. In contrast, the monkeys infected with lower dose showed formation of typical foreign body granulomas characterized by central liquefaction surrounded by chronic inflammatory response. It was concluded that the inflammatory and immune response exerted by the host against cysticerci, in turn, led to histopathological lesions and the resultant clinical signs thereof.